Періодизація середньовічних поселень Лівобережжя гирла Дунаю - Сміленко, А.Т.; Козловський, А.О. (Археологія, 2000)
У статті на підставі польових досліджень 80-х років визначено три періоди існування поселень з певними етнокультурними особливостями, що відображають заселення регіону в часи середньовіччя. В статье определены три периода в жизни средневековых поселений на Левобережье устья Дуная, исследовавшиеся в 80-х годах и частично ранее. Первый период относится к концу VII—VIII вв. Оседлое население в это время малочисленно. Селища единичны, небольшие и недолговременные. Второй период датируется IX — началом X в. Численность оседлого населения в то время возрастает. Увеличиваются размеры поселений и время их существования. Появляется двухрядовая планировка жилищ. Прослеживаются хозяйственные и культовые комплексы, В регионе расселяются и славяне, и праболгары, часто на одних и тех же поселениях, что приводит к интеграции их культуры, проходящей по-разному на отдельных поселениях. Местом расселения славян становится Днестровский лиман — поселение позднего этапа культуры Луки Райковецкой, Шабо и др. Их появление можно связать с началом развития торговли Руси с Византией и курсированием торговых флотилий между Киевом и Константинополем. Одна из остановок флотилий была в устье Днестра. Большое разноэтническое поселение IX — начала X в. у с. Богатое вблизи одного из рукавов устья Дуная содержит материалы, отражающие культуру региона второго периода. Особенностью поселения является значительная концентрация в культуре праболгарского элемента, как следствие второго прихода к Дунаю праболгар после восстания кабаров в Хазарском каганате в начале IX в. Среди поселений региона выделяется более поздняя группа памятников третьего периода, существовавших в X — начале XI в. Их особенность — полуземляночиые жилища с печами-каменками, неизвестными в первом и втором периодах, а также преобладание в керамическом комплексе славянской средневековой керамики с венчиками сложной профилировки (поселения Болград, Нагорное II, Суворово І и др.). На большинстве поселений преобладают славянские черты культуры. Авторы предполагают приход в то время групп уличей с левого берега Днестра на правый после того, как они переместились с Днепра между реками Буг и Днестр. Для уличей были характерны печи-каменки в жилищах, что археологически подтверждает это переселение. Общий вывод для всех трех периодов: частый приход к Дунаю групп разноэтнического населения замедлял процесс интеграции их культуры и создание единой однородной культуры. Левобережье устья Дуная оставалось в эти периоды контактной зоной. The paper defines three periods in the life of the medieval settlements on the left bank of the Danube estuary, which were studied in the 1980s and partly earlier. The first period is referred to the end of the VII - VIII centuries. The settled population was few at that time. Settlements were unique, small, and short-time. The second period is dated by the IX - the turn of the X century. The number of the settled population, sizes of settlements, and time of their existence grew at that time. The two-row planning of settlements had appeared, and economic and cult complexes are traced. The Slavs and proto-Bulgarians settled in the region and frequently in the same settlements, which led to the integration of their cultures carried on differently in separate settlements. The Slavs appeared near the Dniester estuary, in particular, at the settlement of the late stage of the Luka Raikovetska culture, at Shabo, etc., which can be related with the beginning of the trade between the Rus and Byzantine Empire and with the plying of trade flotillas between Kyiv and Constantinople. One of the stops of flotillas was at the Dniester estuary. The large polyethnic settlement of the IX — the turn of the X century at the village of Bogatoe near one of the branches of the Danube estuary gave materials reflecting the culture of the region in the second period. Its peculiarity consists in the significant concentration of the proto-Bulgarian element as a consequence of the second arrival of proto-Bulgarians to the Danube after the revolt of the Kabars in the Khazar Chaganate at the beginning of the IX century. Among the settlements of the region, one may separate a more late group of monuments of the third period, which existed in the X - the turn of the XI century. They are characterized by semi-deepened dwellings with stoves unknown in the first and second periods and the dominance of the Slavic medieval ceramics with rims of a complex profile in the ceramic complex (settlements Bolgrad, Nagomoe II, Suvorovo I, etc.). For most settlements, Slavic features of culture dominated. We suppose that the groups of the Ulichi migrated from the left to right bank of the Dniester, following their resettlement from the Dnieper to the region between the Bug and Dniester rivers. The Ulichi constructed stoves in dwellings, which confirms this migration archaeologically. The common conclusion for all three periods: the frequent arrival of poly-ethnic groups to the Danube slowed down the process of integration of their cultures and the creation of a single uniform culture. In those periods, the left bank of the Danube estuary remained to be a contact zone.